Metabolism and distribution of p,p'-DDT during flight of the white-crowned sparrow, Zonotrichia leucophrys - Scollon, Edward J.; Carr, James A.; Rintoul, David A.; McMurry, Scott T.; Cobb, George P. (My University, 2014)
This study evaluated the interactions of flight, fasting, and 1,1,1-trichloro-bis(4-chlorophenyl)ethane (p,p′-DDT) loading on residue metabolism and distribution in recently exposed white-crowned sparrows (Zonotrichia leucophrys). Female sparrows were dosed with 5 mg p,p′-DDT per kg body weight over 3 d. Following 1 d of recovery, sparrows were flown in a wind tunnel for up to 140 min, in 15-min blocks. Food was withheld from the start of the flight period until birds were euthanized. DDT, 1,1-dichloro-2,2-bis(4 chlorophenyl)ethane (DDD), and 1,1-dichloro-2,2-bis(4-chlorophenyl)ethylene (DDE) were present in all tissues examined. 1-Chloro-2,2-bis(4-chlorophenyl)ethene (DDµ), 1,1-bis(4-chlorophenyl)ethane (p,p′-DDη), and 2,2-bis(4-chlorophenyl)ethanol (p,p′-DDOH) were not found. Fasting did not significantly affect the rate of residue increase over time in any of the tissues examined. When sparrows flew and fasted simultaneously, fasting seldom contributed to an increase in tissue residues. However, the length of time flown was significantly correlated with increasing toxicant concentrations in the brain, kidney, and liver, effectively demonstrating the potential for brief flights to enhance mobilization of DDT and its metabolites. Dose, flight, and fasting also increased residues in brain tissue. These contaminant redistributions may have important ramifications on the stresses experienced by migratory birds.
Keywords: Bioaccumulative compounds; Organochlorines; Avian; Migration; Metabolism